Neurology and the kidney. Issue 6 (1st December 1998) - Burn, D J; Bates, D
Abstract : Renal failure is relatively common, but except in association with spina bifida or paraplegia it is unlikely to occur as a result of disease of the CNS. Renal failure, however, commonly affects the nervous system. The effects of kidney failure on the nervous system are more pronounced when failure is acute. In addition to the important problems related to renal failure there are both acquired and genetically determined diseases which may affect the kidney and the brain. Those acquired diseases include the vasculitides, the paraproteinaemias, and various granulomatous conditions (considered in other chapters of Neurology and Medicine ). In two of the most commonly encountered genetically determined diseases, Von Hippel-Lindau disease and polycystic kidney disease, location of pathogenic mutations will provide improved screening programmes and, possibly, allow therapeutic intervention. Uraemia may affect both the central and peripheral nervous systems. Whereas the clinical features of uraemia are well documented, the pathophysiology is less well understood and probably multifactorial. Uraemic encephalopathy, which classically fluctuates, is associated with problems in cognition and memory and may progress to delirium, convulsions, and coma. The encephalopathy may initially worsen with periods of dialysis and almost certainly relates to altered metabolic states in association with ionic changes and possibly impaired synaptic function. Renal failure may affect the peripheral nervous system, resulting in a neuropathy which shows a predilection for large diameter axons. This may be reversed by dialysis and transplantation. The myopathy seen in renal failure, often associated with bone pain and tenderness, is similar to that encountered in primary hyperparathyroidism and osteomalacia. Dialysis itself is associated with neurological syndromes including the dysequilibrium syndrome, subdural haematoma, and Wernicke's encephalopathy. Dialysis dementia, which was prevalent during the 1970s, has reduced in frequency with the use of aluminium free dialysate. With the introduction of transplantation and the concomitant use of powerful immunosuppressive drugs, the pattern of neurological problems encountered in renal replacement therapy has shifted. Five per cent of patients develop nerve injuries during renal transplantation, and up to 40% of patients experience neurological side effects from cyclosporine. Furthermore, CNS infections, often fungal in type, have been reported in up to 45% of transplant patients coming to postmortem. The nature of the involvement of neurologists with their nephrology colleagues is therefore evolving.